[View of Westman Islands From Eldfell] - Streng, Evelyn Fiedler (1975)
Photograph of Westman Islands from Eldfell. Black and brown hills cover the foreground surrounding the smooth mountain visible along the right edge of the photograph. The grey ocean is just visible through a heavy fog in the distance. In the grey water sits two tan and green islands, the right mountainous while the left island is covered in small hills.